PENGGUNAAN METODE STORYTELLING ISLAMI GUNA MENINGKATKAN KARAKTER JUJUR PADA SISWA DI STTD AL-BIRRU MAJENANG - Alif Fia Damayanti; Amrin Mustofa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using the Islamic storytelling method in improving honest character among second-grade students at STTD Al-Birru Majenang. The Islamic storytelling method was chosen because it can convey moral values and Islamic teachings through stories that are interesting and easy for children to understand. This research uses a Classroom Action Research (CAR) approach, consisting of planning, implementation, observation, and reflection cycles. The subjects of the study were second-grade students participating in Islamic Religious Education lessons. Data were collected through observations, interviews, and documentation of student activities during the learning process. The results show an increase in honest behavior among students after the application of the Islamic storytelling method. Students became more aware of the importance of honesty and demonstrated honest attitudes in their daily activities. In addition, this method also increased students' motivation and enthusiasm in following Islamic Religious Education. The study concludes that the Islamic storytelling method is effective in shaping honest character in second-grade students. It is recommended that teachers implement this method routinely in Islamic Religious Education to optimally develop the students' honest character.